AXILLARY ARTERY INJURY IN BLUNT SHOULDER TRAUMA - AN UNCOMMON ASSOCIATION WITH PROXIMAL HUMERUS FRACTURE - Usman, Rashid; Malik, Hammad; Nadeem, Rana Dilawaiz (Journal of Ayub Medical College Abbottabad, 2019)
Axillary artery injury along with proximal humerus fracture as a result of blunt trauma is a rare incidence. We present a 65-year-old male with a pulseless cold hand, who had blunt trauma 3 days ago, leading to fracture of proximal end of humerus along with axillary artery injury. Surgical intervention revealed contusion of axillary artery with intravascular thrombosis causing complete occlusion. Internal fixation of fracture along with excision of contused axillary artery was done followed by interposition venous graft. The diagnostic modalities and treatment options for such a case are discussed. Keywords: Axillary artery; Trauma; Fracture humerus